2001
DOI: 10.1055/s-2001-16460
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Variation in RGR and the Underlying Traits among 24 Grass Species Grown in Full Daylight

Abstract: A growth analysis was conducted with 24 central European grass species in full daylight to test whether traits underlying interspecific variation in relative growth rate (RGR) are the same in full daylight as they are at lower light, and whether this depends on the ecological characteristics of the studied species, i.e., their requirements with respect to nutrient and light availability. In contrast to studies with herbaceous species at lower light, net assimilation rate (NAR) contributed more than leaf area r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 37 publications
3
32
0
Order By: Relevance
“…dominant (Lambers and Poorter, 1992;Modrzyński et al, 2015;Poorter and Remkes, 1990;Rees et al, 2010;Reich et al, 1992 andWalters et al, 1993;Westoby, 1999, 2000) and NAR-dominant (Huante and Rincon, 1998;Huante et al, 1995;Poorter, 1999;Ryser and Wahl, 2001;Saverimuttu and Westoby, 1996;Shipley, 2006;Taub, 2002), and LMR hardly contributes to RGR (Shipley, 2006). Our results showed three key points.…”
Section: Reaction Of Seedling Growth To the Environmentsupporting
confidence: 50%
“…dominant (Lambers and Poorter, 1992;Modrzyński et al, 2015;Poorter and Remkes, 1990;Rees et al, 2010;Reich et al, 1992 andWalters et al, 1993;Westoby, 1999, 2000) and NAR-dominant (Huante and Rincon, 1998;Huante et al, 1995;Poorter, 1999;Ryser and Wahl, 2001;Saverimuttu and Westoby, 1996;Shipley, 2006;Taub, 2002), and LMR hardly contributes to RGR (Shipley, 2006). Our results showed three key points.…”
Section: Reaction Of Seedling Growth To the Environmentsupporting
confidence: 50%
“…Veenendaal et al 1996;Ryser and Wahl 2001;Shipley 2002). Several studies have shown that relationships among growth parameters depend on the species chosen, in particular, whether variation in RGR is due to variation in shade tolerance or in tolerance of water and/or nutrient stress Ryser and Wahl 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The metaanalysis by Shipley [30] found that NAR was generally the best predictor of RGR, but that as light intensity decreased, the importance of NAR declined and the importance of SLA increased, at least in herbaceous species. The relationship between LMR and RGR is inconsistent, with many a non-significant relationships [31,32]. Therefore, explanations for the variance in RGR between growth forms using the components of RGR are currently contradictory and require further research using approaches that accounts for the effects of plant mass [33].…”
Section: (B) Growth Formsmentioning
confidence: 99%